Revisiting small- and medium-sized enterprises’ innovation and resilience during COVID-19: The tourism sector - Dias, Á.; Cunha, I.; Pereira, L.; Lopes da Costa, R.; Gonçalves, R. (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
Every day, companies are exposed to various risks arising from their environment, and small and medium enterprises (SMEs) are the most affected. This study emphasizes innovation and resilience as the starting points to understand how SMEs are influenced by external factors which are inde-pendent of the managers’ will. To date, we have seen several extreme factors that have conditioned businesses and entrepreneurs of these types of companies, such as the financial crisis of 2008. However, last year, in 2020, we saw the beginning of a worldwide pandemic: COVID-19. Thus, this research seeks to understand the extent to which this pandemic influenced the resilience and in-novation of SMEs in the tourism area. Thus, eight hypotheses were raised based on four inde-pendent variables: access to finance, risk taking, working conditions, and personal network. The study of these variables was developed from an online questionnaire and in-depth interviews. After analyzing the results, it is possible to infer that the COVID-19 pandemic resulted in consequences never observed in previous crises, to such an extent that the study showed that: (1) a company’s network positively influences its resilience; (2) risk taking influences innovation and resilience of these SMEs.